The origins of Oṃ manipadme hūṃ : a study of Kāraṇḍavyūha sūtra - Studholme, Alexander, 1967- (State University of New York Press, 2002)
"Om Manipadme Hum, perhaps the most well-known of all Buddhist mantras, lies at the heart of the Tibetan system and is cherished by both layman and lama alike. This book documents the origins of the mantra, presents a new interpretation of its meaning, and includes a detailed, annotated precis of the Karandavyuha Sutra, opening up this important Mahayana Buddhist work to a wider audience." "The Karandavyuha - the earliest textual source for Om Manipadme Hum - describes both the compassionate activity of Avalokitesvara, the bodhisattva whose power the mantra invokes, and the mythical tale of the search for and discovery of the mantra. Through a detailed analysis of this sutra, Studholme explores the historical and doctrinal forces behind the appearance of Om Manipadme Hum in India at around the middle of the first millennium C.E. He argues that the Karandavyuha has close affinities to non-Buddhist puranic literature, and that the conception of Avalokitsvara and his six-syllable mantra is informed by the conception of the Hindu deity Siva and his five-syllable mantra Namah Sivaya. The sutra reflects an historical situation in which the Buddhist monastic establishment was coming into contact with Buddhist tantric practitioners, themselves influenced by Saivite practitioners."--Jacket